2014
DOI: 10.2139/ssrn.2491995
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Mobile Money in Malawi

Abstract: Bank and the University of New South Wales (UNSW). CIFR is a Centre of Excellence for research and education in the financial sector which is funded by the Commonwealth and NSW Governments and supported by other consortium members, www.cifr.edu.au. We would like to thank Mary Dowell-Jones for her helpful comments. Thanks also to Samuel Gerber, Jessie Ingle, and Nicole Mazurek for excellent research assistance. All responsibility lies with the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Under this situation, if a mobile payment provider collapses, user funds may be at increased risk. History has revealed that companies providing mobile money have experienced such risks of becoming insolvent, lose customers' funds, closing their operations and putting customers at risk (Greenacre, 2020).…”
Section: Risky and Security Issuesmentioning
confidence: 99%
See 4 more Smart Citations
“…Under this situation, if a mobile payment provider collapses, user funds may be at increased risk. History has revealed that companies providing mobile money have experienced such risks of becoming insolvent, lose customers' funds, closing their operations and putting customers at risk (Greenacre, 2020).…”
Section: Risky and Security Issuesmentioning
confidence: 99%
“…Examples include fraud at mobile telephone network Uganda in 2012, collapse of CelPay in 2014 and closure of Orange Mobile in 2017 (Greenacre, 2020).…”
Section: Risky and Security Issuesmentioning
confidence: 99%
See 3 more Smart Citations